Indicadores de soledad y aislamiento en adolescentes de dos provincias del Norte Argentino ; Indicators of Loneliness and Isolation in Adolescents from two Provinces in the North of Argentina - Lacunza, Ana Betina (2017)
El objetivo de este trabajo fue evaluar indicadores de soledad y aislamiento autopercibida por 412 adolescentes escolarizados, residentes en Tucumán y Santiago del Estero (Argentina). Se trató de un estudio comparativo, transversal con muestreo accidental. Se administró el Cuestionario de Aislamiento y Soledad (CAS), la Batería de Socialización (BAS-3) y una encuesta sociodemográfica. El 28% manifestaba comportamientos riesgosos en soledad y 25% en aislamiento. Un 7% refería comportamientos con mayor propensión psicopatológica. El grupo con riesgo en soledad presentaba déficits en habilidades sociales: menor consideración con los demás, menor liderazgo y mayor retraimiento respecto a sus pares sin riesgo; el de riesgo en aislamiento mostraba menor autocontrol. Los datos descriptos identificaron indicadores de vulnerabilidad en población adolescente escolarizada y son valiosos para diseñar estrategias de intervención como prevención. The aim of this paper was to evaluate indicators of self-perceived loneliness and isolation by 412 adolescents attending school and living in Tucumán and Santiago del Estero (Argentina). A comparative, transversal research was carried out and the technique used was accidental sampling. The loneliness and isolation questionnaire (CAS), BAS-3 Socialization Battery and a sociodemographic survey were administered. 28% evidenced risky behaviour in loneliness and 25% in isolation. Within this group, 7% presented a higher psychopathological tendency. The group in loneliness at risk showed lack of social skills related to less consideration for others, a lower degree of eadership and higher degree of withdrawal. On the other hand, the group in isolation at risk evidenced a reduced level of self-control. The data described made it possible to identify indicators of vulnerability in adolescent population who attend school and they proved to be valuable to design intervention strategies as prevention.